Merawat Intelektual dan Kekeluargaan di Bumi Masenrempulu Desa Pundilemo - Imam Permana; Fitriani Kadir; Edy Setiadi; Sri Nur Fira; Nursul Hijriani (KHIDMAH: Jurnal Pengabdian Masyarakat, 2022)
Caring for intellectuals and kinship on earth Masenrempulu Pundilemo Village. The purpose of this service is to provide assistance, empower the community in the implementation of religious development and family values ​​in Pundilemo Village. This community service was carried out for 45 days. The service team carried out the preparation of activities in the form of initial actions, namely approaching local residents, village officials and also conducting surveys for approximately a week as an initial step to develop a work program. The method used is the SWOT (Strengths, Weakness, Opportunities, and Threats) analysis method. The SWOT analysis method is a practical method used to find out the strengths, weaknesses, opportunities and obstacles of each problem. This community service activity has succeeded in growing intellectual and family values ​​in Pundilemo Village, especially in the fields of education, religion, and health. In addition, the community's response is also very good even though the implementation of the work program is still not 100% perfect.